Antena array beam steering untuk sensor synthetic aperture radar (SAR) pada unmanned aerial vehicle (UAV) menggunakan software IE3D - Herli Mia Haqu (PILLAR OF PHYSICS, 2016)
Sensor Synthetic Aperture Radar (SAR) work using the side looking of the system that is useful to distinguish the signal reflections from the left side or the right side at the same distance from the surface of the object or target. SAR sensors are taken using Unmanned Aerial Vehicle (UAV) and mounted on one side of the plane that caused the UAV requires a load balancer. One way to overcome this is to install the antenna under the fuselage, the radiation to be emitted toward the side known as beam steering antenna techniques. This study simulates the design of the antenna array to determine the influence of the dimensions of the antenna on the characteristics of the antenna array. Simulations carried out by varying the length and width of the feeding patch antenna array. The influence of the dimensions antenna on the antenna characteristics are used as a reference in determining the dimensions of the antenna array beam steering antenna characteristics for SAR sensors on the UAV. The software is used in this simulation software IE3D with the type of substrate pillar packing (NPC-H220A) having a dielectric constant of 2.17, thickness of 3.2 mm and a loss δ = 0.0005. Results of this research showed that the greater the length of the patch then it works the lower frequencies and viceversa. While wide-feeding affect the size of the antenna input impedance of the greater width of feeding the input impedance greater viceversa. Based on simulation results that have been done of the obtained reflection coefficient -18.01 dB antenna beam steering with 20° at a frequency of 1.270 GHz, the simulation results satisfy for the antenna of SAR sensors on the UAV